Cultural Conflict in Hong Kong Angles on a Coherent Imaginary (Springer Singapore, 2018)
This book examines how in navigating Hong Kong's colonial history alongside its ever-present Chinese identity, the city has come to manifest a conflicting socio-cultural plurality. Drawing together scholars, critics, commentators, and creators on the vanguard of the emerging field of Hong Kong Studies, the essay volume presents a gyroscopic perspective that discerns what is made in from what is made into Hong Kong while weaving a patchwork of the territory's contested local imaginary. This collection celebrates as it critiques the current state of Hong Kong society on the 20th anniversary of its handover to China. The gyroscopic outlook of the volume makes it a true area studies book-length treatment of Hong Kong, and a key and interdisciplinary read for students and scholars wishing to explore the territory's complexities.